Personality traits, perceived stress and perception of COVID-19 among Arab Population: A cross-sectional survey - Samah Mohamed Taha Eid; Evangeline Del Mundo; Ahmed Hashem El-Monshed (International Journal of Africa Nursing Sciences, 2022)
Background: Coronavirus disease-2019 is a worldwide pandemic. Political authorities are working hard to fight the disease transmission through corresponding interventions that may be influenced by individual perception, perceived stress, and personality traits that act as predictors of healthy behaviors and comply with protective measures especially with different cultures. Aim: This study aimed to assess personality traits, perceived stress, and perception among the Arab population. Methods: A cross-sectional online survey was fulfilled by 948 adults from different Arabic nationalities from 24th June to 15th July 2020. The Ten-Item Personality Inventory (TIPI), the Perceived Stress Scale (PSS), and Perception toward COVID-19 Questionnaire were used in this study. Results: More than three quarters (76.1%) believed that COVID 19 is a dangerous disease and the vast majority (93.1%) disagreed that infection with the virus is associated with stigma. Agreeableness was high among the Egyptians, extroversion and openness to experience were high among Saudi Arabians, while emotional stability was high among Sudanese participants. Conclusion: Individuals with high conscientiousness, extraversion, and emotional stability demonstrated lower levels of perceived stress during the pandemic. This highlights that for the development of stress management interventions during epidemics; it is crucial to take personality traits into consideration.